Preparation and Electrochemical Properties of Tin–Iron–Carbon Nanocomposite as the Anode of Lithium‐Ion Batteries. Issue 11 (12th August 2015) - Yang, Xu; Zhang, Rongyu; Bie, Xiaofei; Wang, Chunzhong; Li, Malin; Chen, Nan; Wei, Yingjin; Chen, Gang; Du, Fei
Abstract Tin–iron–carbon nanocomposite is successfully prepared by a sol–gel method followed by a chemical vapor deposition (CVD) process with acetylene gas as the carbon source. The structural properties, morphology, and electrochemical performances of the nanocomposite are comprehensively studied in comparison with those properties of tin–carbon and iron–carbon nanocomposites. Sheet‐like carbon architecture and different carbon contents are induced thanks to the catalytic effect of iron during CVD. Among three nanocomposites, tin–iron–carbon demonstrates the highest reversible capacity of 800 mA h g−1 with 96.9 % capacity retention after 50 cycles. It also exhibits the best rate capability with a discharge capacity of 420 mA h g−1 at a current density of 1000 mA g−1. This enhanced performance is strongly related to the carbon morphology and content, which can not only accommodate the large volume change, but also improve the electronic conductivity of the nanocomposite. Hence, the tin–iron–carbon nanocomposite is expected to be a promising anode for lithium‐ion batteries.